Art and Artifice in Public Apologies - Boyd, David P. (2011)
The purpose of this article is threefold: to examine the elements of an artful apology; to sequence them in a comprehensive configuration; and to use the taxonomy for assessing the effect of public apologies. The model identifies seven sequential components of an apology: revelation, recognition, responsiveness, responsibility, remorse, restitution, and reform. Also included in the model are four deflective stratagems: dissociation, diminution, dispersion, and detachment. Analysis focuses on actual offense situations rather than artificial simulated settings. Specifically, the study examines whether seven well-publicized apologies conform to the proposed construct. These public figures include Alec Baldwin, Lloyd Blankfein, Jamie Dimon, Gerald Levin, Iris Robinson, Tiger Woods, and Mark Zuckerberg. The article closes with suggestions to direct future research.
Keywords: Public apologies; Pragmatics; Apology components; Apologies